2002
DOI: 10.1038/sj.npp.1300070
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Modulation of Ethanol Consumption in Vesicular Monoamine Transporter 2 (VMAT2) and Dopamine Transporter (DAT) Knockout Mice

Abstract: Several lines of evidence suggest that monoaminergic systems, especially dopaminergic and serotoninergic systems, modulate ethanol consumption. Humans display significant differences in expression of the vesicular and plasma membrane monoamine transporters important for monoaminergic functions, including the vesicular monoamine transporter (VMAT2, SLC18A2) and dopamine transporter (DAT, SLC6A3). In addition, many ethanol effects differ by sex in both humans and animal models. Therefore, ethanol consumption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 109 publications
(115 reference statements)
4
8
0
Order By: Relevance
“…Consistently, animal studies have also shown that reduced DAT expression is a risk factor. For example, mice carrying a reduction in DAT expression display liability for drug addiction [2528]. Both clinical and pre-clinical findings suggest that up-regulation of hDAT , perhaps via modulation of the 121-bp, may alleviate related brain disorders such as substance abuse in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, animal studies have also shown that reduced DAT expression is a risk factor. For example, mice carrying a reduction in DAT expression display liability for drug addiction [2528]. Both clinical and pre-clinical findings suggest that up-regulation of hDAT , perhaps via modulation of the 121-bp, may alleviate related brain disorders such as substance abuse in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Rodent studies have demonstrated that DAT and VMAT2 play important roles in reinforcing behaviors (Hall et al. 2003; Thomsen et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mice lacking VMAT2 show that the homozygote animals die within a few days of birth and heterozygotes have significantly decreased monoamine levels and increased neurotoxicity as well as depressive-like phenotypes (Fon et al, 1997, Takahashi et al, 1997, Wang et al, 1997, Fumagalli et al, 1999, Narboux-Neme et al, 2011). Numerous other preclinical studies have shown that drugs of abuse have robust effects on VMAT2 function/expression, including increased neurotoxicity after methamphetamine exposure (Fumagalli et al, 1999, Uhl et al, 2000, Hall et al, 2003, Savelieva et al, 2006, Fleckenstein et al, 2007, Vergo et al, 2007, Yamamoto et al, 2007, Tong et al, 2008, Fleckenstein et al, 2009, Eiden and Weihe, 2011, Ellis et al, 2011, McFadden et al, 2011a, McFadden et al, 2011b, Vieira-Brock et al, 2011). Caudle et al (2007) observed that mice expressing approximately 5% of normal VMAT2 (VMAT2 LO) display age-associated nigrostriatal dopamine dysfunction accompanied by increased oxidative stress and decreased expression of the dopamine transporter and tyrosine hydroxylase, ultimately leading to neurodegeneration (Caudle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%